A DEBILITATING COMPLICATION OF MEASLES VIRUS: SSPE - Neha Kamran; Fatima Jehangir (ziauddin University, 2019)
Subacute sclerosing panencephalitis (SSPE) is a rare and chronic neurodegenerative disease caused by an unceasing infection of the brain by an altered form of the measles virus acquired earlier in life. The initial symptoms usually involve regressive changes in intellect and personality. Over a span of several months, the psychological symptoms are augmented by neurologial symptoms, which most often composes of myoclonic jerks. This disorder more often affects male children or adolescents as compared to females and adults. SSPE cases are now mostly seen in developing countries where measles virus is still highly prevalent. Here we report a case of a 6 years old male who presented to the Primary Health Care Centre in a small settlement area of Karachi; with complaints of gradual weakness of all four limbs associated with loss of power and mild fever. The boy was also having myoclonus seizures involving right upper arm and right facial jerks. Brain MRI showed no physical abnormality although the Electroencephalogram revealed abnormal signals which confirmed SSPE.